A STUDY ABOUT ANTHELMINTIC EFFECT OF PUNICA GRAMATUM L BARK ON VETERINARY ENDOPARASITES - Thanh Hai, Nguyen; Van Thanh, Nguyen; Thi Tho, Bui; Atsushi, Miyamoto (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The present research was performed to evaluate the anthelmintic activity of Punica gramatum L plant bark on veterinary endoparasites. Method: We used 4 methods to extract the bark of Punica gramatum L plant, including using water, water and heat, water with previous soak in NaOH 5 % and water with previous soak in CH3COOH 5 %. Those solutions then were tested with animal endoparasites, including porcine ascarids, porcine cestodes, chicken ascarids and chicken trematodes at the concentrations of 20, 10, 5, 2.5 and 1.25 %. Their anthelmintic activity was evaluated through the lethal time by which the treatment of extracts induced the death of tested parasites. Result: bark of Punica gramatum L plant possesses anthelmintic efficacy with animal endoparasites. All of extracts at 5 % were able to kill 100% of experimental parasites within the tested time (360 minutes). Extraction with CH3COOH 5 % had the best effect, with the shortest necessary treatment time in all of tested concentrations with 4 experimental endoparasites. Conclusion: Punica gramatum L plant bark has in vitro anthelmintic on porcine ascarids, porcine cestodes, chicken ascarids and chicken trematodes, and follow-up researchs are necessary to assess the in vivo effect. Key words: Punica gramatum L, bark, extract, anthelmintic effect, endoparasites